Knowledge and Compliance among Staff Nurses in Collecting Urine Culture from Patients on Indwelling Catheter in A Medical Ward - Binti Arifin, Norliza; Dioso, Regidor III; Panduragan, Santhna Letchmi (The Malaysian Journal of Nursing (MJN), 2022)
Urine specimens can easily be contaminated by microbes in the genital area, which often leads to false positive results and antibiotic over-prescriptions. This study aimed to evaluate nurses’ knowledge and compliance regarding urine collection with an indwelling catheter in a medical ward. A total of 101 registered nurses participated in this study from September 2020 to January 2021 at the Hospital Raja Perempuan Zainab II (HRPZII). A total of 118 nurses participated in this study. Generally, the nurses had sufficient knowledge of the correct urine specimen handling. Cramer’s V analysis showed a moderate association between hand hygiene knowledge and practice among the nurses (φc: 0.273, p = 0.046). In addition, the knowledge and practice of decontaminating continuous bladder drainage areas displayed a relatively moderate association (p = 0.01). While most nurses showed knowledge of the contamination preventive measures, initiatives should be taken so that all nurses would be more likely to comply with the recommended procedure and reduce specimen contamination.